Control pairings of a deoiling membrane crossflow filtration process based on theoretical and experimental results. (September 2019) - Jepsen, Kasper L.; Pedersen, Simon; Yang, Zhenyu
Highlights: Reduced fouling potential by considering control pairings. Relative gain array method was used to analyse cross couplings. The different control pairings were compared numerically and experimentally. A pilot plant was used to experimentally test the considered pairings. Accounting for control loops interactions improved control performance. Abstract: Despite membrane filtration being extensively used in many industries, it is not widely used for offshore produced water treatment because of the large installation footprint required. Commonly, PID-controllers are deployed to maintain the operating conditions that minimize fouling, but the design of the controllers is rarely highlighted. The interaction between the deployed controllers can cause undesired performance and even instability. In this study, the relative gain array method was used to find the set of control pairings that minimized the interaction between the control loops. Experimental results showed that by accounting for cross couplings in the design phase of the control system, the controllers performance in terms of reference tracking can be improved significantly. By improving the reference tracking and disturbance rejection capabilities of the filtration system, the selected operating point which minimizes fouling growth, can be maintained consistently subject to disturbances in terms of varying feed flow rate. Better tracking of the operating point can reduce membrane resistance, and consequently reducing the operating cost.